Gore Techs59th Venice Biennale, curated by Cecilia Alemani, Venice, Italy, 23 April–27 November 2022. Issue 2 (13th April 2023) - Crivellaro, Tricia; Heller, Lynne
Review of: Gore Techs 59th Venice Biennale, curated by Cecilia Alemani, Venice, Italy, 23 April–27 November 2022